Concordance between physician-rated and caregiver-perceived disease severity in children with atopic dermatitis : a cross-sectional study - Xu, Xiaomeng (2021)
This study examined concordance between caregiver-reported and physician-rated estimates of severity of atopic dermatitis (AD) in paediatric patients and explored potential explanatory factors. Physician-reported severity of AD was retrieved from medical records, while caregiver-reported disease severity and sociodemographic data were obtained through a survey that also collected information on out-of-pocket expenses due to AD. There was 38.5% (95% confidence interval (95% CI) 30.1, 43.5) disagreement between physician and caregivers with regards to both underestimating and overestimating the condition. A duration since AD diagnosis shorter than 6 months showed higher concordance (kappa: 44.4%; 95% CI 30.6, 58.2) between caregiver and physician estimates of AD severity compared with a duration of 6 months or longer. Caregivers underestimating their child’s AD accounted for 27.7% among all participants, while 10.8% overestimated the severity of AD compared with physicians. Factors significantly associated with caregiver’s underestimation of disease severity were age of the child and time since disease diagnosis. Comparison of concordance between caregiver-reported and physician-rated estimates of severity of AD in paediatric patients revealed a tendency amongst caregivers to underestimate severity of AD. This information may have clinical implications for treatment outcomes if caregivers fail to adhere to medical advice.